The Students’ Interest on the Use of Vocabulary Self-Collection Strategy in Learning English Vocabulary - Syayyidina Ali (Universitas Cokroaminoto Palopo, 2017)
The learning should be supported by an interesting strategy to make students enjoyable and interested in learning, as well as in learning English Vocabulary. The aim of this research is to investigate and describe the students’ perceptions on the use of vocabulary self-collection strategy in Learning English vocabulary. This study was a descriptive model consisting of 37 subject-students. The data were collected with a questionnaire, it was rating scale which distributed after 8 meetings of treatments, and it covered 15 positive and closed statements about the use of vocabulary self-collection strategy in learning vocabulary classroom. The questionnaire was analyzed based on the percentage of each answer. To calculate questionnaire data into percentage, the researcher used the formula where the number of frequency is multiplied to 100% then divided to the number of the total respondents. The result of the students’ perceptions indicated that vocabulary self-collection strategy is interesting strategy used in learning vocabulary classroom. The highest rank of the mean score is 56.6% of agree students, 35.5% of strongly agree students, 6.7% of undecided students, 0.7% of disagree students, and 0.2% of strongly disagree to the statements on the questionnaire.